Consortin: a potential modulator of ventricular conduction. (19th May 2022) - Marsman, EMJ; Offerhaus, JA; Bosada, FM; Beekman, L; Christoffels, VM; Boukens, BJ; Remme, CA; Bezzina, CR
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Consortin, encoded by the CNST gene, is a ubiquitously expressed protein putatively involved in trafficking of connexins to the plasma membrane. In the heart, connexins form gap junctions, which are essential for cardiac conduction. Reduced levels and abnormal cellular distribution of connexins have been found in patients with heart failure, atrial fibrillation, arrhythmogenic cardiomyopathy and Brugada syndrome. Purpose: To decipher the role of Consortin in cardiac electrophysiology. Methods: Homozygous Cnst knockout mice (Cnst-/-) were generated using CRISPR-Cas9 technology. Consortin expression was assessed by Western blot analysis. Cardiac conduction parameters were recorded by electrocardiography in anesthetized wild-type (WT) and Cnst-/- male and female littermates aged 3-6 months. Conduction velocity (CV) was determined in Langendorff-perfused hearts by optical mapping of the right ventricle (RV) at a pacing cycle length of 120 ms. Data were analyzed by Student's t-test and P values < 0.05 were considered significant. Results: Western blot analysis confirmed the presence of Consortin in WT mouse hearts, and its absence in Cnst-/- hearts. Heart rate, P-wave duration and PR-interval did not differ between groups, whereas QRS interval was significantly prolonged in Cnst-/- (mean±SEM 8.7±1.3 ms, n=13) compared to WT mice (7.9±1.1ms, n=13; (p=0.0009)). Hearts were structurally normal, and heart weight:body weight ratio was similar between groups. Preliminary optical mapping at the RV of Langendorff-perfused hearts demonstrated a lower, although not significantly different, transversal CV in Cnst-/- (56±4.3 cm/s, n=6) compared to WT (65±7.1 cm/s; n=3; p=0.31), whereas longitudinal CV was similar between groups (Cnst-/- 80±4.2 cm/s versus WT 83±9.1 cm/s; p=0.74). No differences were observed in RV effective refractory period (p=0.59). Conclusion: These preliminary findings support a modulatory role of Consortin in ventricular conduction. Current efforts are aimed at elucidating the underlying electrophysiological and molecular mechanisms, including the impact of Consortin on cardiac connexins.